ChemInform Abstract: Rapid Synthesis of Substituted Pyrrolines and Pyrrolidines by Nucleophilic Ring Closure at Activated Oximes. Issue 11 (8th March 2013) - Chandan, Nandkishor; Thompson, Amber L.; Moloney, Mark G.
Abstract Substituted pyrrolidines are synthesized by ring closure initiated by direct nucleophilic attack of stabilized enolates at the nitrogen of oximes (I), (IV), (VII) and (IX) activated with an appropriate leaving group.